Recent Topical Research on Global, Energy, Health & Medical, and Tourism Economics, and Global Software: An Overview - Chang, Chia-Lin; McAleer, Michael (Journal of Reviews on Global Economics, 2017)
The paper presents an overview of recent topical research on global, energy, health & medical, and tourism economics, and global software. We have interpreted â€œglobalâ€ in the title of the Journal of Reviews on Global Economics to cover contributions that have a global impact on economics, thereby making it "global economics". In this sense, the paper is concerned with papers on global, energy, health & medical, and tourism economics, as well as global software algorithms that have global economic impacts. The topics covered include re-opening the Silk Road to transform Chinese trade, education and skill mismatches, code of practice and indicators for quality management of official statistics, projections of energy use and carbon emissions, multi-fuel allocation for power generation using genetic algorithms, optimal active energy loss with feeder routing and renewable energy for smart grid distribution, demand for narcotics with policy implications, computer technology to improve medical information, heritage tourism, ecotourism impacts on the economy, society and environment, taxi drivers’ cross-cultural communication problems and challenges, hybrid knowledge discovery system based on items and tags, game development platform to improve advanced programming skills, quadratic approximation of the newsvendor problem with imperfect quality, classification of workflow management systems for emails, academic search engine for personalized rankings, creative and learning processes using game-based activities, personal software process with automatic requirements traceability to support start-ups, and comparing statistical and data mining techniques for enrichment ontology with instances.